CHANGES IN SPARE PARTS PRICES, CUSTOMER SATISFACTION AND PROFITABILITY STRATEGY AT PT ASTRA INTERNATIONAL TBK - TSO AUTO2000 MT HARYONO WORKSHOP - Nabil Yazid Hasan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The Indonesian automotive industry is experiencing significant growth, driving an increasing demand for after-sales services, including spare parts. However, fluctuations in spare part prices pose a challenge that can impact customer satisfaction and the sustainability of workshop profitability. This study aims to analyze the impact of spare part price changes on customer satisfaction and the profitability strategies implemented by Auto2000 MT Haryono, Balikpapan. A qualitative case study was used. Data were collected through structured interviews with five respondents—four customers and one workshop manager—and non-participant observation during an internship. Data analysis was conducted using thematic analysis techniques. The results show that changes in spare part prices elicit an initial reaction of surprise from customers, but do not directly reduce satisfaction levels if communication is conducted openly and responsively. Customer satisfaction is largely determined by service quality, information transparency, and established loyalty. Conversely, centrally controlled price adjustments can actually increase workshop profitability when accompanied by compensation strategies such as the Toyota Care program and seasonal promotions. This study concludes that balancing clear price communication and increasing service value is key to maintaining customer satisfaction and sustainable profits. This study provides practical contributions to workshop management in designing customer-oriented pricing and communication strategies, and opens up opportunities for further exploration in other automotive workshop contexts.